2008
DOI: 10.1093/ajcn/87.5.1268
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four–hour analysis of elevated energy expenditure after physical activity in a metabolic chamber: models of daily total energy expenditure

Abstract: These results suggest that EPEE has a small effect on 24-h EE in the course of normal daily activities, findings that do not support the proposition by the Institute of Medicine for estimating TEE. However, persons with low physical fitness levels could enhance EE as EPEE by increasing vigorous-intensity daily physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
1
14
0
2
Order By: Relevance
“…Basal metabolic rate (BMR) was determined as the mean metabolic rate between 0715 and 0800. Coefficient of variation (CV) for BMR over 3 days was 1.7% as previously reported [11]. Prescribed physical activity in L-day consisted of 30 min of walking at 3.2 km/h, 30 min of walking at 5.6 km/h, and 15 min of jogging at 8.0 km/h.…”
Section: Methodssupporting
confidence: 59%
“…Basal metabolic rate (BMR) was determined as the mean metabolic rate between 0715 and 0800. Coefficient of variation (CV) for BMR over 3 days was 1.7% as previously reported [11]. Prescribed physical activity in L-day consisted of 30 min of walking at 3.2 km/h, 30 min of walking at 5.6 km/h, and 15 min of jogging at 8.0 km/h.…”
Section: Methodssupporting
confidence: 59%
“…The gold standards to measure energy expenditure (EE) are direct calorimetry and doubly labeled water (Ohkawara et al 2008;Snodgrass et al 2006). In addition to their very expensive and unsuitable use for everyday purposes, these two methods have the major disadvantage of offering no information on the frequency and intensity of the spontaneous activity of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…When we discuss issues concerning total EE induced by exercise, we need to investigate not only duration of the exercise, but also the post-exercise recovery period. During this period, there is a remarkable increase in EE due to the excess post-exercise energy expenditure (EPEE) ( 15 ), also known as the excess post-exercise oxygen consumption (EPOC) ( 4,9 ). Many studies ( 2,6,9 ) have revealed that exercise intensity impacts the magnitude of EPEE.…”
mentioning
confidence: 99%